Dubinin’s Theory: A Versatile Tool in Adsorption Science - Stoeckli, Fritz; Lavanchy, A.; Hugi-Cleary, Deirdre (My University, 1998)
Ce travail présente la théorie de Dubinin, ses conséquences en calorimétrie d'immersion ainsi que des développements recents. En particulier, la description des isothennes de type V par I'équation de Dubinin-Astakhov (vapeur d'eau sur les charbons actifs) et la combinaison avec la theorie de Myers et Prausnitz qui conduit à une description de l’adsorption multiple en régimes statique et dynamique. La théorie de Dubinin inclut également l’adsorption de vapeurs par certains solides non poreux., The paper presents the main features of Dubinin's theory for the volume-filling of micropores, its direct consequences in the field of immersion calorimelry and recent developments such as the possibility to describe type V isotherms (water on active carbons) with the Dubinin-Astakhov equation, and to deal with multiple adsorption under static and dynamic conditions. It also confirmed that in some cases Dubinin's theory applies to adsorption by non-porous surfaces.